2010
DOI: 10.1007/s00508-010-1420-3
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous coronary intervention of an anomalous right coronary artery originating from the left coronary artery

Abstract: Anomalous origin of the right coronary artery is a rare congenital anomaly that was first described in 1948 by White and Edwards. It is well established that an anomalous origin of the right coronary artery can lead to angina pectoris, myocardial infarction, or sudden death, in the absence of atherosclerosis. Thus from the literature data it has been also suggested that the abnormal origin and course of anomalous coronary arteries could make them more prone to atherosclerosis due to altered flow patterns. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…It is more difficult to perform PCI in SCA anomaly patients than in patients without coronary anomaly. It is known that the incidence of stent restenosis and thrombosis after PCI is higher in these patients than in the normal population (9). This could be the reason for stent thrombosis in our patient who had an anomalous RCA arising from the mid-LAD.…”
Section: Discussionmentioning
confidence: 65%
“…It is more difficult to perform PCI in SCA anomaly patients than in patients without coronary anomaly. It is known that the incidence of stent restenosis and thrombosis after PCI is higher in these patients than in the normal population (9). This could be the reason for stent thrombosis in our patient who had an anomalous RCA arising from the mid-LAD.…”
Section: Discussionmentioning
confidence: 65%
“…Cardiovascular magnetic resonance (CMR) is a suitable alternative investigation for assessing coronary anatomy. Advantages extended by CMR include lack of exposure to ionizing radiations, no need to use iodinated or ionized intravenous contrast media, no restrictions imposed by body habitus, simultaneous evaluation of multiple parameters of cardiovascular anatomy, perfusion and function, along with the ability to achieve high spatial and temporal resolutions to better assess structural abnormalities [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Awareness of those variations is important for catheter-based treatment. Rudan et al [ 13 ] successfully performed PCI with stent placement in a case of SCA where RCA originated as extension of left coronary vasculature. Kafkas et al [ 15 ] reported successful stent placement in an L1 type SCA.…”
Section: Discussionmentioning
confidence: 99%
“…Since manifestation varies from benign to sudden death depending on situation, multiple treatment options should be considered including medical, interventional, or surgical procedures 18). Recently, a report suggested that an anomalous coronary artery should be followed without intervention and stated that the benefit of excessive exercise limitation is doubtful.…”
Section: Discussionmentioning
confidence: 99%